Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 4 - Calculating the Derivative - 4.3 The Chain Rule - 4.3 Exercises - Page 225: 11


$f[g(x)]=\sqrt{8x^{2}-4}$ $g[f(x)]=8x+10$

Work Step by Step

In the expression for f(x), replace x with g(x) $f[g(x)]=\sqrt{g(x)+2}$ $=\sqrt{(8x^{2}-6)+2}$ $=\sqrt{8x^{2}-4}$ In the expression for g(x), replace x with f(x) $g[f(x)]=8(f(x))^{2}-6$ $=8(\sqrt{x+2})^{2}-6$ $=8x+16-6$ $=8x+10$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.